Multiple Credit Rating: Triple Rating under the Requirement of Dual Rating in Korea. Issue 14 (14th November 2021) - Ryoo, Juyoun; Lee, Cheolwoo; Jeon, Jin Q.
ABSTRACT: The paper investigates a unique phenomenon where triple rating gained popularity while dual rating is required in Korea. Triple rating may improve information production by introducing increased competition among CRAs (credit rating agencies) while it may exacerbate rating inflation through more rating shopping and rating catering on the ground of greater bargaining power shifted toward the issuer. We examine the effect of triple rating on rating inflation, information production, and rating changes. Triple rating on average has a lower rating and a greater information production effect than dual rating after controlling for endogeneity. The rating level appears to be a significant factor in shaping the future rating mandates in triple rating. The propensity that splits are resolved through rating upgrades in triple rating significantly existed but has noticeably faded away since the strict regulatory changes in 2009.